2011
DOI: 10.1002/acr.20648
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of disease burden over five years in a multicenter inception systemic lupus erythematosus cohort

Abstract: Objective. We describe disease activity, damage, and the accrual of key autoantibodies in an inception systemic lupus erythematosus (SLE) cohort. Methods. The Systemic Lupus International Collaborating Clinics (SLICC) International Research Network, comprising 27 centers from 11 countries, has followed an inception cohort of SLE patients yearly according to a standardized protocol. Of these patients, 298 were followed for a minimum of 5 years and constitute the study population. Disease activity was assessed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(122 citation statements)
references
References 11 publications
4
111
1
6
Order By: Relevance
“…The Euro-Lupus study revealed that European patients, the majority of whom are Caucasians, are characterized by a lower frequency of the organ manifestation of SLE compared to patients from Asia, and North and South America [2,6]. This observation was also confirmed by other authors [5,22]. Moreover, the results of another multicenter European study [11] suggest that the activity of SLE can also differ within the same continent.…”
Section: Discussion Demographic and Clinical Characteristicsmentioning
confidence: 60%
See 2 more Smart Citations
“…The Euro-Lupus study revealed that European patients, the majority of whom are Caucasians, are characterized by a lower frequency of the organ manifestation of SLE compared to patients from Asia, and North and South America [2,6]. This observation was also confirmed by other authors [5,22]. Moreover, the results of another multicenter European study [11] suggest that the activity of SLE can also differ within the same continent.…”
Section: Discussion Demographic and Clinical Characteristicsmentioning
confidence: 60%
“…At enrollment in the study, patients with a history of obstetric failures did not differ significantly from the remaining women in terms of median SELENA SLEDAI score (8 [4][5][6][7][8][9][10][11][12] vs. 8 [4][5][6][7][8][9][10][11][12] T Ta ab bl le e I IV V. . Prevalence of active involvement or injury of various organs/systems determined on the basis of SLE Activity Index (n = 269)…”
Section: Obstetric Failuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Urowitz и соавт. [29], анализируя ре-зультаты наблюдения 298 больных в течение 5 лет, устано-вили, что высокая активность СКВ отмечается в дебюте; в течение пяти последующих лет она снижается под воз-действием лечения, но за этот период значительно увели-чивается число НП.…”
Section: данные когортных исследований и регистров за рубежомunclassified
“…Physicians currently manage SLE with multiple immunosuppressive medications that improve disease control, some of which may also put patients at risk for potential severe side effects from broad immunosuppression [Askanase et al 2009;Carneiro and Sato, 1999]. Moreover, patients may continue to develop disease flares despite what appears to be optimal treatment, requiring escalation of therapy including increased use of corticosteroids and possibly contributing to subsequent long-term damage [Urowitz et al 2012]. Thus, there continues to be a need for more effective and safe options to treat SLE.…”
Section: Introductionmentioning
confidence: 99%